Perancangan Model Enterprise Architecture Planning pada PT. Bestari Kalimantan - Zulfani, Muhamad; Emanuel, Andi Wahju Rahardjo (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
PT Bestari Kalimantan is a contracting company specializing in network installation. Currently, the system used is still manual and not computerized for data management, including employee payroll, equipment and inventory processing, and other data. In this technological era, adopting a computerized system is crucial for companies to support the smooth flow of their business processes. Therefore, at PT. Bestari Kalimantan, an Enterprise Architecture Planning has been designed, encompassing a Strategic Plan for the computerized system, aiming to assist in optimizing business processes. From the results of the Enterprise design, proposals for applications have been generated that can be used by PT. Bestari Kalimantan to replace the current manual system. With the Blueprint from the Enterprise Architecture design, it is hoped that PT. Bestari Kalimantan can enhance its service to customers